Odpowiedź :
B) P = 4cm * 1,5cm = 6cm P = 40mm * 15mm = 600mm
P = 6 cm kwadratowych P = 600mm kwadratowych
Więc 6cm kwadratowych = 600 mm kwadratowych
C). P = 4 cm * 2 cm = 8 cm P = 40 mm * 20 mm = 800 mm
P = 8 cm kwadratowych P = 800mm kwadratowych
Więc 8cm kwadratowych = 800 mm kwadratowych
P = 6 cm kwadratowych P = 600mm kwadratowych
Więc 6cm kwadratowych = 600 mm kwadratowych
C). P = 4 cm * 2 cm = 8 cm P = 40 mm * 20 mm = 800 mm
P = 8 cm kwadratowych P = 800mm kwadratowych
Więc 8cm kwadratowych = 800 mm kwadratowych